Sudden emergence of a Neisseria gonorrhoeae clade with reduced susceptibility to extended-spectrum cephalosporins, Norway. Issue 12 (17th December 2020) - Osnes, Magnus N.; Didelot, Xavier; Korne-Elenbaas, Jolinda de; Alfsnes, Kristian; Brynildsrud, Ola B.; Syversen, Gaute; Nilsen, Øivind Jul; De Blasio, Birgitte Freiesleben; Caugant, Dominique A.; Eldholm, Vegard
Abstract : Neisseria gonorrhoeae multilocus sequence type (ST)-7827 emerged in a dramatic fashion in Norway in the period 2016–2018. Here, we aim to shed light on the provenance and expansion of this ST. ST-7827 was found to be polyphyletic, but the majority of members belonged to a monophyletic clade we termed PopPUNK cluster 7827 (PC-7827). In Norway, both PC-7827 and ST-7827 isolates were almost exclusively isolated from men. Phylogeographical analyses demonstrated an Asian origin of the genogroup, with multiple inferred exports to Europe and the USA. The genogroup was uniformly resistant to fluoroquinolones, and associated with reduced susceptibility to both azithromycin and the extended-spectrum cephalosporins (ESCs) cefixime and ceftriaxone. From a genetic background including the penA allele 13.001, associated with reduced ESC susceptibility, we identified repeated events of acquisition of porB alleles associated with further reduction in ceftriaxone susceptibility. Transmission of the strain was significantly reduced in Norway in 2019, but our results indicate the existence of a recently established global reservoir. The worrisome drug-resistance profile and rapid emergence of PC-7827 calls for close monitoring of the situation.